Human Papillomavirus T-Cell Cross-reactivity in Cervical Cancer: Implications for Immunotherapy Clinical Trial Design - Helman, Sarah R. (JAMA Netw Open, 2018)
IMPORTANCE: Clinical trials are testing vaccines that target human papillomavirus 16 (HPV-16) oncoproteins for the treatment of cervical cancer regardless of the HPV type of the tumor. For patients with HPV-18–positive cancers, this strategy relies on cross-reactivity of HPV-16–reactive T cells against the HPV-18 oncoproteins. OBJECTIVES: To determine the prevalence of HPV-16 and HPV-18 metastatic cervical cancers in women enrolling in clinical trials at a US medical center and to assess whether HPV oncoprotein–targeting tumor-infiltrating lymphocytes (TILs) and T-cell receptors (TCRs) possess HPV-16/HPV-18 oncoprotein cross-reactivity. DESIGN, SETTING, AND PARTICIPANTS: This study was conducted at the National Institutes of Health Clinical Center, a tertiary care research hospital in the United States. The HPV type of the tumors from 65 consecutive patients with cervical cancer who were evaluated for participation in clinical trials was determined by retrospective medical record review. Immunological assays testing HPV cross-reactivity were conducted on all available archived samples of oncoprotein-reactive TILs from HPV-positive tumors (n = 16) and on a library of previously identified TCRs (n = 10). INTERVENTIONS: The HPV genotype of each patient’s tumor was determined. The cross-reactivity of archived TILs and a library of TCRs was assessed. MAIN OUTCOMES AND MEASURES: The main outcomes were the prevalence of each HPV genotype and the frequency of TILs or TCRs with HPV oncoprotein–T-cell cross-reactivity. Cross-reactivity was assessed by enzyme-linked immunospot assays and interferon-γ production assays. RESULTS: The median (range) age of 65 referred patients was 44 (24-64) years. Ethnicity was recorded for 39 of 65 patients; 35 (89.7%) were white, 3 (7.7%) were Asian, and 1 (2.6%) was American Indian/Alaskan Native. Histologic tumor subtype was recorded for 41 of 65 patients; 25 (61.0%) were squamous cell carcinomas, 12 (29.3%) were adenocarcinomas, 2 (4.9%) were adenosquamous cell carcinomas, and 2 (4.9%) were neuroendocrine tumors. Thirty-nine of 65 patients (60.0%) had HPV-16–positive tumors and 21 patients (32.3%) had HPV-18–positive tumors. In the analysis of cross-reactivity, 1 of 16 oncoprotein-reactive archived TILs (9 from cervical cancers and 7 from other cancers) displayed HPV-16/HPV-18 cross-reactivity. None of the 10 oncoprotein-reactive TCRs displayed HPV-16/HPV-18 cross-reactivity. CONCLUSIONS AND RELEVANCE: Cervical cancers that tested positive for HPV-18 were common in this study and may be common in other US clinical trial populations. Results showed that HPV-16/HPV-18 intergenotype T-cell cross-reactivity of T cells from HPV-16–positive and HPV-18–positive cancers was uncommon. These findings support clinical trial designs in which the HPV type targeted by a therapeutic vaccine is matched with the HPV type of a cancer and suggest a change is necessary in the design of active clinical trials.